(untitled) (Repertorio Científico, 2024)
During the taxathon carried out in November 2017 at the La Sabana Metropolitan Park, a list of aquatic macroinvertebrates was made, using the taxonomic classification system. Several segments of the lagoon perimeter were sampled using a D-type net and hand strainer (both with 0.5 mm mesh pore), as well as a handnet. All possible microhabitats were reviewed, including hard land banks, muddy banks, grassy banks, cement edges, areas with aquatic plants, vegetation roots, silty bottoms, under rocks or logs, and on the surface of the water. Several of the identified taxa are described. A total of twelve orders were found in the first sampling, distributed in six taxonomic classes of aquatic macroinvertebrates; on the other hand, for the second sampling a total of twelve orders were found, distributed in eight taxonomic classes of macroinvertebrates. The lagoon has a lentic habitat condition, that is, it does not have a circulation process except the effect of the breeze on the surface. This causes their oxygenation conditions to be minimal. Although the diversity found, so far, does not represent a public health hazard, it is necessary to adopt measures to recover said habitat to improve it and the environment.